Organization Development Intervention Towards Effective and Efficient Performance of the Presbyterian University of East Africa (Puea) Kikuyu Campus, Kenya East Africa - Gichung’wa, Miriam Wanjiku (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2015)
This study was on Organization development interventions on the effectiveness and efficiency as a means of increased performance of an organization the case of Presbyterian University of East Africa (PUEA). The research was both descriptive and comparative in nature done in four phases: Assessment of the Organization, OD Interventions, Monitoring and implementation and finally evaluation of the identified problems. The pre and post intervention data was collected from 25 staff who was involved in the study through administering of a 35 questions questionnaire, observation and interviews on specific people. The focus was on VMGS, Structure, Process, People and Technology. The t-test and p-value analysis showed a significance change leading to the rejection of the null hypothesis. The study concluded that the Intervention activities brought about the effective and efficient performance at PUEA. Further, it is an indicator that with the full implementation of the strategic plan, PUEA would achieve optimum performance. Based on the outcome and for continuity and sustainability, the study recommends that all the organizational development intervention activities done in the VMGS, Structure, Process, People and Technology should be institutionalized in the organization practices for increased performance.